Blood Work : Life and Laboratories in Penang - Carsten, Janet (Book collections on Project MUSE., 2019)
Janet Carsten traces the multiple meanings of blood as it moves from donors to labs, hospitals, and patients in Penang, Malaysia, showing how those meanings provide a gateway to understanding the social, political, and cultural dynamics of modern life.